Competition between coherent ultrafast energy redistribution and photochemistry in the collective strong coupling regime: the role of static disorder - Mellini, Federico; Vendrell, Oriol (The journal of physical chemistry letters, 2025)
We explore the dynamics of coherent, ultrafast energy redistribution in disordered molecular ensembles mediated by a cavity under electronic strong coupling and their competition with the onset of a photochemical process. Quantum dynamics simulations show that the amount of energy redistribution between different molecules depends on their individual coupling strength to the cavity. This collective dynamical process is determined by the initial state of the system and by the relative time-scales of the Rabi-cycling and the onset of the photoreaction. Even in the large ensemble limit, where each molecule is weakly coupled, the relative reaction probability of each individual molecule differs significantly from its reaction probability in an uncoupled ensemble, which is due to the dynamic energy reorganization promoted by the cavity. We investigate this mechanism by considering different types of initial conditions of a disordered ensemble of tens of NOCl molecules, each treated in full dimensionality. The multilayer multiconfiguration time-dependent Hartree method is used to describe the ensemble and the cavity.